Value based selling - Melkman, Alan (Henry Stewart Talks, 2010)
Key questions, How organizations work and create value, Value creation, The organizational value chain, Value propositions, Customer management hierarchy, The Decision Making Unit (DMU), Contact base issues, Developing the contact strategy, From salesperson to consultant, Why salespeople don't ask more questions, Customer value, Quality or return, Total price or investment, Value based selling